Microsurgical Management of Tuberculum Sellae Meningiomas by the supraorbital keyhole eyebrow approach: Surgical Outcome - Bhattarai, Robin; CaoFeng, Liang; Ying, Guo (Nepal Journal of Neuroscience, 2017)
The aim of this study was to evaluate (surgical) visual outcomes in patients treated via supraorbital keyhole eyebrow incision approach. Data from 14 patients with TSMs (Tuberculum Sellae Meningioma) who underwent microsurgical treatment by a supraorbital keyhole eyebrow skin incision between September 2006 and September 2013 were retrospectively collected and analyzed. Patients were analyzed on the basis of clinical, radiological, and surgical factors that appeared to affect the outcome. To quantify the extent of ophthalmological disturbances Visual impairment score was used to analyze visual acuity and visual fields, which range from 0 (best) to 100 (worst). Change in visual function was assessed as the main outcome. The mean age of the 10 women and 4 men enrolled in the study was 56.50years (range, 42 74 years). The presenting symptom was asymmetrical visual loss in 71.4% of the patients. And examination revealed decreased visual acuity (Snellen notation) in 100% and impaired visual fields (Goldmann perimetry) in 58.3 % (7/12 cases, central scotoma and temporal anopia n=1, classical bitemporal hemianopia n=4, incongruent homonymous hemianopia n=2 , 2 cases data N/A) of the patients. Simpson grades I resection via a supraorbital keyhole eyebrow skin incision approach, were achieved in 100% of the patients. Quality of life was assessed according to Karnofsky scale and was 86.67 (range: 70 100). The mean follow-up duration was 51.73 months (range: 27 91 months).No recurrent tumors were observed during this period. According to the findings of this study, this approach provides a pleasing cosmetic outcome and also decreases brain manipulation while minimizing the likelihood of procedure-related morbidity. A favorable visual outcome was observed in most of the patients in the late postoperative period. Nepal Journal of Neuroscience, Volume 14, Number 3, 2017, page : 26-32